THE EFFECTIVENESS OF PSS (PLAYS, STORIES, SONGS) METHOD IN LEARNING ENGLISH AS A FOREIGN LANGUAGE: AN EXPERIMENTAL STUDY AT STATE MADRASAH IBTIDAIYAH 1 OF PALEMBANG - Richway Richway (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2015)
The purpose of this study is to determine the effectiveness of the PSS method in teaching English as a foreign language at State Madrasah Ibtidaiyah 1 of Palembang. This study is also to determine the effect of PSS method in improving student learning outcomes.This research is a quantitative researchusingthe classes that already exist as a group, both for the experimental class and the control class, which is estimated at the same condition. The experimental study class consisted of 36 students and a control class also consists of 36 students.The result of the analysis show that the experimental class of 36 students on average score of 4.5 on the learning outcomes of pre-test and 5.97 at post-test. While the control class scored on average of 4.91 on the learning outcomes of the pre-test and 4.97 at post-test. The results of the SPSS hypothesis analysis that has been done in the paired samples t-test show that the mean of the experimental group is -1.472 with standard deviation 2.131. And t value is -4.145, while significant (2-tailed) of 0.000˂0.05. It can be concluded that rejected Ho, and can be said that there is a significant difference of students’ achievement before and after the application of PSS method.